Leisure-time physical activity in the vicinity of Academias da Cidade Program in Belo Horizonte, Minas Gerais State, Brazil: the impact of a health promotion program on the community - Amanda Paula Fernandes; Amanda Cristina de Souza Andrade; Cynthia Graciane Carvalho Ramos; Amélia Augusta de Lima Friche; Maria Angélica de Salles Dias; César Coelho Xavier; Fernando Augusto Proietti; Waleska Teixeira Caiaffa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract This study analyzed leisure-time physical activity among 1,621 adults who were non-users of the Academias da Cidade Program in Belo Horizonte, Minas Gerais State, Brazil, but who lived in the vicinity of a fitness center in operation (exposed Group I) or in the vicinity of two sites reserved for future installation of centers (control Groups II and III). The dependent variable was leisure-time physical activity, and linear distance from the households to the fitness centers was the exposure variable, categorized in radial buffers: < 500m; 500-1,000m; and 1,000-1,500m. Binary logistic regression was performed with the Generalized Estimation Equations method. Residents living within < 500m of the fitness center gave better ratings to the physical environment when compared to those living in the 1,000 and 1,500m buffers and showed higher odds of leisure-time physical activity (OR = 1.16; 95%CI: 1.03-1.30), independently of socio-demographic factors; the same was not observed in the control groups (II and III). The findings suggests the program's potential for influencing physical activity in the population living closer to the fitness center and thus provide a strategic alternative for mitigating inequalities in leisure-time physical activity.